The secret of Raven Point : [large type] a novel - Vanderbes, Jennifer (Wheeler Publishing, 2014)
"1943: When seventeen-year-old Juliet Dufresne receives a cryptic letter from her enlisted brother and then discovers that he's been reported missing in action, she lies about her age and travels to the front lines as an army nurse, determined to find him. Shy and awkward, Juliet is thrust into the bloody chaos of a field hospital, a sprawling encampment north of Rome where she forges new friendships and is increasingly consumed by the plight of her patients. One in particular, Christopher Barnaby, a deserter awaiting court-martial, may hold the answer to her brother's whereabouts--but the trauma of war has left him catatonic. Racing against the clock, Juliet works with an enigmatic young psychiatrist, Dr. Henry Willard, to break Barnaby's silence before the authorities take him away. Plunged into the horrifying depths of one man's memories of combat, Juliet and Willard are forced to plumb the moral nuances of a so-called just war and to face the dangers of their own deepening emotional connection" -- from publisher's web site.